2016
DOI: 10.1089/scd.2016.0147
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating GAA Repeat Induced Transcriptional Silencing of the Friedreich's Ataxia Gene During Somatic Cell Reprogramming

Abstract: Friedreich's ataxia (FRDA) is the most common autosomal recessive ataxia. This severe neurodegenerative disease is caused by an expansion of guanine-adenine-adenine (GAA) repeats located in the first intron of the frataxin (FXN) gene, which represses its transcription. Although transcriptional silencing is associated with heterochromatin-like changes in the vicinity of the expanded GAAs, the exact mechanism and pathways involved in transcriptional inhibition are largely unknown. As major remodeling of the epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…Amplification of GAA repeat expansions in the FXN gene was performed by PCR using primers GAA_F: and GAA_R: as previously described [ 26 , 28 , 29 ]. Amplifications were conducted in 40 or 50μL reactions containing 50-200ng of DNA template.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification of GAA repeat expansions in the FXN gene was performed by PCR using primers GAA_F: and GAA_R: as previously described [ 26 , 28 , 29 ]. Amplifications were conducted in 40 or 50μL reactions containing 50-200ng of DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the results obtained from patient tissues, the mouse tissues showed an expansion bias, particularly in the cerebellum and DRG, as well as an age-dependent increase in mutation load [ 17 , 23 ]. Lastly, in vitro studies on cultured immortalized lymphoblast cell lines and induced pluripotent stem cells (iPSCs), obtained by reprogramming of FRDA fibroblasts, demonstrated somatic instability when serially passaged [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of FRDA patients are homozygous for expanded GAA trinucleotide repeats in the first intron of the frataxin (FXN) gene. The expanded GAA repeats impede transcription of the FXN gene leading to severe downregulation of its mRNA and protein levels [5,6]. Frataxin (FXN) is a small mitochondrial protein involved in the regulation of iron homeostasis and the biosynthesis of iron-sulfur clusters (Fe-S).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological Modulation during Somatic Cell Reprogramming. Another recently evaluated strategy was based on the hypothesis that the epigenetic modifications close to GAA repeats present in Friedreich's ataxia can be reversed by pharmacological modulation during somatic cell reprogramming [55]. In this study, researchers induced the generation of pluripotent stem cells by reprogramming Friedreich's ataxia fibroblasts in the presence of various small molecules that target DNA methylation as well as histone acetylation and methylation.…”
Section: Dna Targeting Strategiesmentioning
confidence: 99%
“…In this study, researchers induced the generation of pluripotent stem cells by reprogramming Friedreich's ataxia fibroblasts in the presence of various small molecules that target DNA methylation as well as histone acetylation and methylation. Treatment of these stem cells with two compounds (sodium butyrate and Parnate [tranylcypromine]), led to increased expression of the frataxin gene, which persisted for several passages [55]. However, they observed that prolonged culture of those epigenetically modified cells resulted in progressive expansion of triplet repeats and a consequent decrease in gene expression.…”
Section: Dna Targeting Strategiesmentioning
confidence: 99%